2005
DOI: 10.1042/bj20041344
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic processing and glycosylation influence formation of porcine prion protein complexes

Abstract: High level of heterogeneity seems to be a ubiquitous feature of mammalian PrPs (prion proteins) and may be relevant to the pathogenesis of prion diseases. In the present study, we describe the heterogeneity of PrP(C) (cellular form of PrP) from porcine brain. It was disclosed and characterized by a combination of one-dimensional PAGE and two-dimensional PAGE analyses with enzymic deglycosylation and copper-affinity experiments. We found that the identified two main populations of porcine PrP(C) consist of digl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…autolysis of cells, pH value [15], redox potential etc., may have unpredictable effects on PrP structure and immunogenicity. This is not surprising, since a recent study suggests that the majority of PrP C in pig brain appears in a fully-glycosylated form [38]. We observed that PrP C isolated from uninfected and infected murine brain appeared predominantly to be diglycosylated.…”
Section: Discussionsupporting
confidence: 62%
“…autolysis of cells, pH value [15], redox potential etc., may have unpredictable effects on PrP structure and immunogenicity. This is not surprising, since a recent study suggests that the majority of PrP C in pig brain appears in a fully-glycosylated form [38]. We observed that PrP C isolated from uninfected and infected murine brain appeared predominantly to be diglycosylated.…”
Section: Discussionsupporting
confidence: 62%
“…Heterogeneity of PrP C proteins is enhanced by endogenous proteolytic modifications, which occurs in vivo [25–27]. PrP C from non‐infected brains consists in addition to full‐length PrP to a significant amount of an N‐terminal truncated PrP C fragment termed C1.…”
Section: Resultsmentioning
confidence: 99%
“…Copper and heparan sulfate binding have been mediated through its N‐terminal domain [22,23]. However, under physiological conditions the N‐terminal region can be lost by cleavage [23–28]. From endogenous proteolysis, cleavage sites in human PrP C were mapped at amino acids 110–112 and at residues 80–100 generating N‐truncated forms; these are referred to as C1 and C2, respectively.…”
mentioning
confidence: 99%
“…In some cells, however, such as neurons in the hippocampus, thalamus, and neocortex, the cytosol form of PrP C is commonly found. 21 Both membrane-bound and soluble forms of PrP C are found in the cerebral spinal fluid. 22 Membrane-bound PrP C can be secreted from cells into the extracellular matrix (ECM) in exosomes, and Martins and coworkers 23 list a number of mechanisms for the release of soluble PrP C from the GPI anchor at the cell membrane.…”
mentioning
confidence: 99%
“…215 Further, PrP C may also be involved in other melanocortin diseases such as collagen-related disease (of the eye), 216 pigmented collagen disease of the synovium (involving p53 regulation of monocytes), 217 and thyroid disease. 218 The link between PrP C , αMSH, and NF-κB suggests that the neuroprotective role of PrP C could play a part in the anesthetic response of elderly patients who suffer postanesthetic dementia (Alzheimer's disease), 219,220 possibly involving the role of PrP C in cytoskeleton organization, 21,122 an important focus for further investigation.…”
mentioning
confidence: 99%